Their agriculture, our agriculture: applying critical Latin American agroecological thought to England / Sua agricultura, nossa agricultura: aplicando o pensamento agroecológico crítico da América Latina à Inglaterra / Su agricultura, nuestra agricultura: aplicando el pensamiento agroecológico crítico latinoamericano a Inglaterra - Cardwell, Emma (REVISTA NERA, 2022)
Agroecology research on the Global North is recognised by scholars in the Global South as technical and environmental, ignoring the political dimensions of agroecological movements and change. This article applies the epistemological traditions of critical Latin American agroecology to a Global North case study: England, in the United Kingdom. As the origin nation of capitalist industrial agriculture, the application of Latin American agroecological thought can tell us a lot about the dynamics of the English situation, colonialism, and the barriers to agroecological transition.